2005
DOI: 10.1088/0957-4484/16/9/032
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nanoelectrodes for neurophysiology: cathodic electrophoretic paint insulation and focused ion beam milling

Abstract: The fabrication and characterization of tungsten nanoelectrodes insulated with cathodic electrophoretic paint is described together with their application within the field of neurophysiology. The tip of a 127 μm diameter tungsten wire was etched down to less than 100 nm and then insulated with cathodic electrophoretic paint. Focused ion beam (FIB) polishing was employed to remove the insulation at the electrode's apex, leaving a nanoscale sized conductive tip of 100-1000 nm. The nanoelectrodes were examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Furthermore, recording contacts are always opened at the tips of the carbon fibers, and it is not possible to make them along the shank of the fibers with this method. To increase control over geometry of the recording sites, we applied focused ion beam (FIB) milling (Qiao et al 2005) (Helios NanoLab; FEI) to selectively remove the insulation. FIB is a nanomanufacturing technique that utilizes a high-energy ion beam that is focused on the surface of the specimen to produce extremely fine details (working resolution below 10 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, recording contacts are always opened at the tips of the carbon fibers, and it is not possible to make them along the shank of the fibers with this method. To increase control over geometry of the recording sites, we applied focused ion beam (FIB) milling (Qiao et al 2005) (Helios NanoLab; FEI) to selectively remove the insulation. FIB is a nanomanufacturing technique that utilizes a high-energy ion beam that is focused on the surface of the specimen to produce extremely fine details (working resolution below 10 nm).…”
Section: Methodsmentioning
confidence: 99%
“…al. [103] demonstrated that 700 nm tipped electrode recorded wellisolated action potentials extracellularly from single visual neurons in vivo. Further experimental studies using sub-100 nm silicon nanowires revealed its integration into live cells without causing detrimental effects.…”
Section: Nanodevices In Neurological Surgery Proceduresmentioning
confidence: 99%
“…Finally one also needs to design electrodes with tip size below 1 lm. Although this can be presently achieved using filamented glass with micropipette puller, nanotechniques such as focused ion beam microscopy (Qiao et al 2005) or carbon nanotubes (Krapf et al 2006) are very promising approaches to produce finer electrodes with a better control. Remarkably, such electrodes will not only enable to patch tiny processes, but shall also contribute to a better signal to noise ratio due their high resistance, as well as minimize deformation of tissue (Scanziani and Häusser 2009).…”
Section: New Optical Approaches For Monitoring Pap Structure and Funcmentioning
confidence: 99%